Implementation of Artificial Intelligence and Interactive Multimedia in Physical Education Instruction at Senior High Schools in Surakarta - Agus Mukholid; Andri Arif Kustiawan (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2026)
Digital transformation in education requires teachers to possess the competence to utilize technology to improve learning quality. However, the use of Artificial Intelligence (AI) and interactive multimedia in Physical Education learning at senior high schools remains limited due to teachers’ insufficient digital competence. This community service program aimed to enhance the digital competence of Physical Education teachers through the implementation of Artificial Intelligence and interactive multimedia to support digital learning transformation in senior high schools in Surakarta. The program employed a Participatory Learning and Action (PLA) approach consisting of four stages: needs assessment, training, implementation assistance, and monitoring and evaluation. The participants were 25 Physical Education teachers from senior high schools in Surakarta. Data were collected through observations, interviews, documentation, and pretest–posttest questionnaires, then analyzed using descriptive statistics and qualitative analysis. The results showed that the teachers’ average digital competence increased from 48.0% before the program to 88.4% after the program, representing an improvement of 40.4%. Participants successfully developed various digital learning products, including 25 AI-assisted teaching modules, 22 interactive presentation media, 20 digital quizzes, 18 instructional videos, 25 AI-based question banks, and 10 Physical Education learning websites. Furthermore, participant satisfaction reached 92.4%, indicating that the assistance program effectively addressed teachers’ needs in implementing digital learning. The program demonstrates that mentoring in the use of Artificial Intelligence and interactive multimedia can enhance teachers’ digital competence while fostering more innovative, interactive, and student-centered Physical Education learning